Capital Flows to Central and Eastern Europe - Milesi-Ferretti, Gian (IMF Working Papers; Working Paper ;, 2006)
We examine the evolution of the net external asset positions of Central and Eastern Europe (CEEC) countries over the past decade, with a strong emphasis on the composition of their international balance sheets. We assess the extent of their international financial integration, compared with the advanced economies and other emerging markets, and highlight the salient features of their external capital structure in terms of the relative importance of FDI, portfolio equity, and external debt. In addition, we briefly describe the country and currency composition of their external liabilities. Finally, we explore the implications of the accumulated stock of external liabilities for future trade and current account balances.